Clostridium septicum septicaemia in a patient with Leukaemia - Hassan, H.; Teh, A. (Stamford Publishing Pte Ltd / Singapore Medical Association, 1994)
Clostridium septicum infection has been shown to have a strikingly high association with either bowel or blood malignancies. The infection may be fatal if unrecognised. We report a case of C. septicum bacteremia in a man diagnosed with acute myeloid leukaemia.